Integrative Morphometrics Using 3D Imaging (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2025)
Three-dimensional morphometrics -- the quantitative characterisation of biological shape in three dimensions using geometric morphometrics, micro-CT scanning, photogrammetry, and structured-light scanning -- has transformed comparative anatomy, systematics, and functional ecology by enabling precise, reproducible shape quantification from complete or partial specimen data. This study presents an integrated 3D morphometric framework applied to 4,284 museum specimens across 247 vertebrate species spanning birds, mammals, fish, and reptiles, combining micro-CT scanning with surface photogrammetry and geometric morphometrics to characterise cranial, appendicular, and postcranial morphological variation. Three-dimensional geometric morphometric analysis using 84-landmark cranial configurations resolved species-level morphological differentiation with 94.7% correct species assignment in 10-fold cross-validated linear discriminant analysis -- substantially exceeding 2D landmark analysis of the same specimens (78.4% correct assignment). Phylogenetic signal in 3D cranial shape was strong (Blomberg's K = 1.47 +- 0.24) across the 247-species dataset, with functional modules (neurocranium, face, palate) showing different rates of evolutionary divergence that reflect the distinct selective pressures acting on sensory versus feeding functions. Micro-CT-derived bone density and trabecular architecture metrics revealed significantly different functional loading environments in aquatic versus terrestrial species within convergently evolved lineages, demonstrating the power of internal 3D structure for inferring functional ecology beyond external shape. The full 3D surface scan and micro-CT dataset is deposited in MorphoSource and constitutes the largest publicly available 3D vertebrate comparative morphology dataset yet assembled.